Effect of light intensity on celery growth and flavonoid synthesis - Qin, Yanmei; Liu, Xuanxuan; Li, Chunyan; Chu, Qianwen; Cheng, Shaobo; Su, Lihong; Shao, Dalong; Guo, Xin; He, Zhongqun; Zhou, Xiaoting (Frontiers in Plant Science, 2024)
Abstract：Light is one of the important environmental factors affecting the growth and development of facility vegetables. In this experiment, we investigated the effects of different light intensities on the growth, nutritional quality and flavonoid accumulation of celery under hydroponic and full LED light conditions. Four light intensities of 40, 100, 200, or 300 µmol•m -2 •s -1 were set up in the experiment, and three harvest periods were set up on the basis of different light intensities, which were 15, 30, and 45 d after treatment (labeled as S1, S2, and S3, respectively). With the increase of light intensity, the plant height and aboveground biomass of celery increased, while the light intensity of 200 µmol•m -2 •s -1 was favorable for increasing the content of chlorophyll, carotenoids, total phenols, vitamin C, cellulose, total flavones and apigenin in celery. During the S1-S3 period, the activities of PAL, CHS, CHI and ANS increased gradually under 200 and 300 μmol•m -2 •s -1 light intensity treatments, and the activities of FNS and CHS enzymes were the highest under 200 μmol•m -2 •s -1 light intensity treatment. The expression and ANS activity of Ag3GT, a key gene for anthocyanin synthesis, reached the maximum value at 300 μmol•m -2 •s -1 , and the expression level and FNS activity of AgFNS, a key gene for apigenin synthesis, reached a maximum value at 200 μmol•m -2 •s -1 . In general, the anthocyanin content was the highest at 300 μmol•m -2 •s -1 , and the apigenin content was the highest at 200 μmol•m -2 •s -1 . In conclusion, light intensity of 200 µmol•m -2 •s -1 treatment was more favorable for celery growth and nutrient synthesis.